Palliative Reconstructive Surgery May Improve Quality of Life In High Functioning Noncurable Head and Neck Oncologic Patients. (May 2015) - Rankin, Timothy; Mailey, Brian; Suliman, Ahmed; Dobke, Marek
Abstract : Background: Treatment recommendations for palliative patients are guided by functional status and individual needs. The projected success of palliative procedures relies on estimating the risk: benefit ratio, which weighs the expected improvement in life quality to the frailty, metabolic status, and the individual's ability to heal after surgery. Terminal patients have less time in which to judge outcomes; therefore, the timeframe in which we assess these metrics should be modified according to prognosis. We emphasize efficiency over simplicity for reconstructive palliative surgery. Methods: We reviewed the literature and supply a representative case to contribute our experiences for the palliative reconstructive surgeon to use in the evaluation and treatment of incurable patients. Results: Palliative reconstructive surgery carries higher perioperative risk than standard reconstructive surgery; however, aggressive surgical management can improve quality of life. We find the Palliative Performance Scale—a functional, prognostic tool—to be a helpful metric for preoperative evaluation. Conclusions: Reconstructive palliative surgery can improve quality of life in dying patients (ie, pain, wound hygiene, and so on) and may even improve survival. We advocate prioritizing efficiency in completing the reconstructive process, which may not be the simplest or least invasive.